(2E)-2-(4-Hydroxy-3-methoxybenzylidene)hydrazinecarboxamide - Tahir, M. Nawaz (International Union of Crystallography, 2012)
In the title compound, C(9)H(11)N(3)O(3), two molecules are present in the asymmetric unit in which the 4-hydroxy-3-methoxybenzaldehyde and hydrazinecarboxamide units are almost planar [with r.m.s. deviations 0.0212 and 0.0066 Å, respectively, in one molecule and 0.0346 and 0.0095 Å, respectively, in the other] and are oriented at dihedral angles of 9.7 (3) and 16.6 (3)°. In both molecules, two S(5) ring motifs are present due to N—H⋯N and O—H⋯O hydrogen bonds. In the crystal, the molecules are dimerized with each other due to pairs of N—H⋯O hydrogen bonds, forming an R (2) (2)(8) ring motif. O—H⋯O hydrogen bonds lead to the formation of a three-dimensional network.